2018
DOI: 10.3390/f9060293
|View full text |Cite
|
Sign up to set email alerts
|

Planting Density and Site Effects on Stem Dimensions, Stand Productivity, Biomass Partitioning, Carbon Stocks and Soil Nutrient Supply in Hybrid Poplar Plantations

Abstract: In this study, planting density and site effects on hybrid poplar productivity and stem dimensions were evaluated on the mid-term and longer term (8 and 14 years) in southern Québec (Canada). We also evaluated the effects of planting density and site on biomass accumulation and carbon stocks in different plantation compartments, on biomass partitioning at the stand-level, on soil carbon stocks and on soil nutrient supply rate after 14 years. The experimental design consisted of three replicate poplar stands lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 60 publications
(100 reference statements)
4
17
0
3
Order By: Relevance
“…Previous field studies with planted poplars have reported different conclusions related to the effect of abiotic and biotic factors on fine root biomass 3538,40,41 . Our regional-scale study, conducted in 14 year-old closed-canopy poplar plantations, provides evidence supporting the negative relationship hypothesis between soil fertility and fine root biomass 13 (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous field studies with planted poplars have reported different conclusions related to the effect of abiotic and biotic factors on fine root biomass 3538,40,41 . Our regional-scale study, conducted in 14 year-old closed-canopy poplar plantations, provides evidence supporting the negative relationship hypothesis between soil fertility and fine root biomass 13 (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…A recent greenhouse study also showed that a low N supply changed gene expression, modified root architecture and led to an increase in fine root biomass, thus providing evidence of a unique nitrogen-adaptative mechanism regulating hybrid poplar root growth in response to soil N supply 39 . Yet, only a few field studies partly support this finding in older plantations 35,40,41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stand density is one important aspect of forest management (Eldegard et al 2019). Strategies have been forwarded to get larger individual growth and higher yield per unit area (Sun et al 2018) in young forest plantations, but recent studies have found that different stand densities can also affect soil C storage (Noh et al 2013;Hernández et al 2016;Na et al 2017;Truax et al 2018Sun et al 2018. To date, studies have primarily focused on how stand density influences soil C in tree plantations on agricultural lands (Fernández-Núñez et al 2010;Scott et al 2006;Sitters et al 2013;Hernández et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, it has been noted that clear-cut harvesting of natural forest has resulted in soil C losses because of reduced C inputs, accelerated decomposition and erosion (Jandl et al 2007;Mayer et al 2017). In order to investigate the influence of tree density on the preservation and promotion of soil C stocks following the harvesting of natural forests, tree plantations at different densities are being established (Truax et al 2018;Mayer et al 2020). This land-use change from natural forests to plantations is likely to influence the soil C pool by shifting litter quality and quantity as well as soil nutrients under managed ecosystems with different vegetation composition and community structure.…”
mentioning
confidence: 99%